Os caminhos da educação e a educação para os caminhos: a formação de engenheiros em São Paulo (1835-1850) - Paula, Odair Aparecido de (2011)
In this research, is had as object i ve to study the creation of the Cabinet Topographico, an establishment of Public Instruction, destined to the con s t i t ution of a center of geodesic studies of the Province of São Paulo. Created in 1835, in a period little studied by History and Brazilian and São Paulo educational historiography, the Topographico Cabinet was formed for a library, a quantity of plants and maps of the Province of São Paulo and a school for formation of engineers of roads. With this work it is intended to contribute with the history of the Brazilian and São Paulo education, filling a gap of the Public Ins t r uction of the Imperial Period. The Topographico Cabinet was the oldest establishment of Instruction of Engineering of the Province of São Paulo and played an important role in the configuration of the city of São Paulo and of the Pr ovince, it was as instrument of knowledge or being able of the São Paulo government. The Engineer of Roads, as course of professional format i o n , i f c h a r a c t e r ized as one of mos t r i g i d o f t h e time, which had to i t s s h or t period of duration, init i ally two years and lat e r three, while other est ablishments of Brazil and the exterior, in the same period, had a minimum schedule load five year. Although the ephemeral life, the Topographico Cabinet constituted an important page of the admi n i s t r a t i o n o f the Province of São Paulo and some of its egresses had acted in diverse sectors of the pol i t i c s and the economy of the Provinc e . I t s e ngineers had contributed for the construction and magnifying of ways of communication of the Province (soil roads) that later they had lost space for the railroads, an English innovation